Experi-vivências antirracistas: propostas de boas práticas educativas (entre 1 a 3 anos) na educação infantil em Uberlândia/MG pós-pandemia - Santiago, Suélen Garcia (2023)
The present dissertation addresses Early Childhood Education in the scenario of the pandemic caused by the New Coronavirus Disease (COVID-19), with emphasis on the importance of approaching the racial theme in the school context of municipal education in Uberlândia, Minas Gerais, Brazil, as a possible dialogue between school, children and their families. The research presented to the Postgraduate Program in Communication, Technologies and Education at the Faculty of Education at the Federal University of Uberlândia (PPGCE/FACED/UFU) also sought to discuss the effectiveness of education for ethnic-racial relations in Early Childhood Education, under participatory and experienced research from the perspective of a pedagogical analyst in the period of remote teaching in 2020, in the hybrid modality in 2021 and in person in 2022, whose field of analysis was the anti-racist practices of an institution of Early Childhood Education in the aforementioned municipality. The methodology was based on the assumptions of qualitative research, focusing on the exploratory and descriptive objectives necessary for this study. In this way, our investigation presents, at first, the panorama of pandemic under the logic of Brazilian education, in which the guiding principle refers to the understanding of the work carried out by public educational establishments in Minas Gerais, especially in Uberlândia, by evidencing the specifications of this process and the isolation between the school and its students, which allowed us to rethink the pedagogical practices allied to the difficulties in doing online teaching for students from one to three years old. In a second moment, our reflection was based on the gaps present in Early Childhood Education, a reflection of the Covid-19 pandemic, and the possibility of an ethnic-racial approach as an inclusive process for children in the period of returning to school. Our foundation for building the proposed narrative comprised the legal-normative framework around Law n. 10,639, of 2003, which establishes the mandatory teaching of Afro-Brazilian history and culture; studies on education in the pandemic; and researches related to race relations education. Through this work, we carried out a pedagogical intervention in the months of October and November 2022 at the aforementioned teaching institution, in order to show how anti-racist educational practices can be implemented through pedagogical practices in Early Childhood Education, by integrating children and their families in the school space with consciousness of combating racism and racial prejudice. We conclude that pandemic provoked reflections on the use of technologies in education and, in the Early Childhood Education modality, it was not effective, due to the age of children and the interaction of family members in the homeschooling process; therefore, in the return to the face-to-face modality, teachers needed to recover sociability, mutual cooperation and respect for individualities and differences in children, including in the context of respect for differences, inclusion of such people in the school context and collective educational activities.